Kajian Pengaruh Penggunaan Semen Ekspos sebagai Finishing Dinding Interior terhadap Psikologis Pengguna Ruang - Rakandenu, I Gede Made Gani; Wardhani, Dyah Kusuma (Aksen : Journal of Design and Creative Industry, 2021)
The use of exposed cement materials as wall finishing lately is in great demand and is becoming a design trend at the moment. Many property buildings ranging from commercial buildings such as cafes, restaurants, to hotels to residential buildings such as houses, apartments and condos use exposed cement as one of the interior wall finishing. Exposed cement as wall finishing is usually associated with industrial design styles. In Indonesia, exposed cement is applied as finishing material after bricks. Using exposed cement as wall finish that nowadays has been trending in architecture and interior applicants gives a different ambience of space, home or building yet still economically acceptable. The using of exposed cement as wall finish are close to the using of industrial style. As known, industrial style is an interior architecture design style that adopting industries elements such as the using of metal, bricks and pipe material then be exposed on purpose. Industrial style has color palette such as black and greyish. Therefore the using of exposed cement as wall finish often used in industrial design style. However with the popular use of exposed cement as wall finish does not mean that it can freely acceptable in all situations, because it can affect the comfort of the room user.